Desempenho agroeconômico do bicultivo de rúcula consorciada com beterraba em função de quantidades de flor-de-seda e arranjos espaciais - Oliveira, Kássya Jemima Borges de (Universidade Federal Rural do Semi-Árido, 2014)
The experiment was conducted at the Experimental Farm 'Rafael Fernandes' of the Universidade Federal Rural do Semi-Árido (UFERSA), located in the district of Alagoinha, from August 2012 to February 2013 with the objective of evaluating the agrieconomic performance of the beet and arugula intercropped as a function of roostertree amounts incorporated into the soil and spatial arrangements of the component crops. The experimental design was of randomized complete blocks with five replications, with the treatments arranged in a 4 x 3 factorial scheme. The treatments consisted of the combinations of four amounts of roostertree incorporated into the soil (10, 25, 40 and 55 t ha-1 of dry matter) and three spatial arrangements (2B:2A, 3B:3A and 4B:4A), corresponding rows of beet (B) alternated with rows of arugula (A). The characteristics evaluated in the beet were: plant height, number of leaves per plant, total and commercial productivity, productivity of classified roots, fresh and dry mass of shoot; in the arugula were: plant height, number of leaves per plant, dry mass of shoot and yield of green mass; in the diagnostic leaves of beet and arugula were evaluated the contents of N, P, K; in the soil were assessed the amounts of bacterial and fungal colonies present before and after planting, as well as, the nutrient contents: N, P, K, pH, CEC and soil organic matter before and after sowing. In the intercropping systems were evaluated the productive efficiency index, the canonical variable score, gross income, net income, rate of return and profit margin. The highest agrieconomic performance of the intercropping beet and arugula was obtained in the amount of 55 t ha-¹ of roostertree incorporated into the soil and in the spatial arrangement of 2B: 2A. The amount of fungi and bacteria of the soil increased with increasing amounts of roostertree added to the soil in the arrangement of 2B: 2A. The multivariate method compared to the univariate method applied to the productive efficiency index was quite effective in determining the best arrangement 2B: 2A of the bicropping of arugula intercropped with beet. It is economically viable for the farmer to use the roostertree as green manure in the beet production intercropped with arugula
Agroeconomic performance of arugula in bicropping intercropped with beet in function of amounts of roostertree and spatial arrangements
Keywords: Green manure; Beta vulgaris L .; Calotropis procera; Intercropped cultivation; Eruca sativa; Adubação verde; Beta vulgaris L.; Calotropis procera; Cultivo consorciado; Eruca sativa; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA